Failed diplomacy : the tragic story of how North Korea got the bomb - Pritchard, Charles L. (Washington, D.C. : Brookings Institution Press, 2007)
'Offers an insider's analysis of developments on the Korean peninsula and how North Korea was able to develop nuclear weapons. Provides a first-hand account of how the Six-Party Talks were initiated, with a step-by-step review of each round of negotiations, detailing the national interests of the key players'--Provided by publisher
Preface -- Prelude to crisis -- Part I : The Role of Rhetoric : getting to yes -- Confrontation over highly enriched uranium -- Influencing the Bush team -- Establishing a multilateral framework -- Part II : Origin of the six-party talks -- Washington and Seoul : a falling out -- The players -- Part III : Six-party talks -- Six party talks : a scorecard -- Rounds four and five : false start or cause for optimism? -- Consequences and accountability -- Missiles, nukes, and talks -- Bilateral engagement with Pyongyang : the record -- Establishing a permanent security forum -- Epilogue -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Notes -- Index
Includes bibliographical references (p. 205-218) and index
Keywords: Nuclear nonproliferation -- Korea (North); Nuclear weapons -- Korea (North); United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States